Morphological, thermal and physicochemical characteristics of small granules starch from Mirabilis jalapa L - Pumacahua-Ramos, Augusto [UNESP]; Demiate, Ivo Mottin; Schnitzler, Egon; Bedin, Ana Claudia; Telis-Romero, Javier [UNESP]; Lopes-Filho, Jose Francisco [UNESP] (Elsevier B.V., 2015)
Some physicochemical and thermal properties of starch from Mirabilis jalapa L, seeds were evaluated. The starch was extracted after hulling and grinding the seeds and the flour obtained was suspended in 0.1% (m/v) NaOH solution for 12 h at 30 degrees C; it was then centrifuged, re-suspended, washed with deionised water and dried in an oven with circulating air at 40 degrees C for 12 h. The micro-images of starch granules were performed by using scanning electron (SEM) and non-contact atomic force microscopy (NC-AFM) techniques; X-ray diffraction and mid-infrared spectroscopy were both used to evaluate the relative crystallinity of the starch granules. Thermal analyses TG/DTG and DSC, were applied for the analysis of thermal behaviour of this starch and the cooking behaviour of its aqueous solution was studied by using a viscometer RVA. Thermogravimetry showed that once dehydrated, the starch was stable up to 292 degrees C after which two steps of decomposition occurred, which were attributed to decomposition and oxidation of organic matter, respectively. The gelatinisation temperature and enthalpy, as assessed by DSC analysis, were 82.1 degrees C and 5.67 J g(-1), respectively. RVA analysis showed pasting temperature of 76.4 degrees C, with a low viscosity peak at 95 degrees C, low breakdown, and high tendency to retrograde during cooling. Microscopic results reveal that the starch granules had a spherical shape and 67.4% of them presented diameters smaller than 890 nm. The X-ray diffractogram showed a typical A-type pattern and a relative crystallinity of 34% with a FTIR of 1047/1022 cm(-1) and a ratio of 1.38.
Keywords: Differential scanning calorimetry; Thermogravimetry; X-ray diffractometry; Mirabilis jalapa starch